Fortalecimiento de la conciencia fonológica mediante la aplicación del programa LOLE del lenguaje oral al lenguaje escrito en un niño con retraso lector de tercer grado de la unidad educativa del milenio Bernardo Valdivieso, 2023 - Robles Ochoa, Christian Joel (2023)
The present curricular integration work was built with the general objective: Strengthen phonological awareness through the application of the LOLE program from oral language to written language in a child with reading delay of third grade of the Millennium Educational Unit Bernardo Valdivieso, 2023. For its development, the use of a mixed, descriptive and cross-sectional approach was considered, with a case study method. For the diagnosis of reading difficulty, the PECO Phonological Knowledge Assessment Test was used. The results found after the evaluation determine that the direct score of syllabic knowledge is 8 and phonemic knowledge is 6, giving a total of 14, which places it in a decile score of 2 and that, according to the test corresponds to a low level of phonological awareness. With the application of the LOLE program from oral language to written language, it was possible to obtain positive changes in the levels of syllabic and phonemic knowledge, key factors for the development of reading.